农牧交错地区生态环境建设与相关政策研究 = The development of optimal environmental economy and policy studies in the agriculture and pasture area - 李忠 Li, Zhong (2008)
This study aims to analysis the causes of desert expansion in the areas of mixed agriculture and pasture.